UPAYA MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN DENGAN MENGGUNAKAN STRATEGI PEMBELAJARAN INSTAN ASSESSMENT SISWA KELAS III SDN 005 PAGARAN TAPAH DARUSSALAM KABUPATEN ROKAN HULU - Gusliwaty Gusliwaty (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2017)
This research is motivated by the lack of learning outcomes students' reading comprehension, particularly on the subjects of Indonesian. For that research by applying instant learning strategy assessment, the purpose of this research is to improve the ability of third-grade students' reading comprehension SDN 005 Pagaran Tapah Darussalam Rokan Hulu. This research is a class act, committed in Tapah Pagaran SDN 005 Darussalam. The subjects were students of class III with a number of students as many as 33 people. This study was conducted in two cycles, each cycle stages in this study were: 1) planning, 2) action, 3) observation, and reflection. The results of the study before action learning outcomes of students' reading comprehension only reached 66.62% in the medium category. In the first cycle of learning outcomes students 'reading comprehension has reached 70.14%, although it has not reached mastery individuals or groups, but the learning outcomes of students' reading comprehension in the first cycle increased from 66.62% to 70.14%. After the improvements on the activities of teachers and students in the second cycle, students' reading comprehension learning outcomes achieved quite satisfactory to reach an average of 77.70%. This situation shows that the improvement of learning on the subjects of Indonesian to use the Instant learning strategy assessment was successful.